2011
DOI: 10.1016/s0140-6736(11)61097-0
|View full text |Cite
|
Sign up to set email alerts
|

Global epidemiology of hepatitis B and hepatitis C in people who inject drugs: results of systematic reviews

Abstract: Background Injecting drug use (IDU) is an important risk for viral hepatitis transmission. Detailed, transparent estimates of the scale of the problem at regional and global levels have never been made. We report national, regional and global prevalence and population size estimates for hepatitis C (HCV) and hepatitis B (HBV) among people who inject drugs. Methods Systematic search of peer-reviewed (Medline/Embase/PsycINFO) and grey literature databases, conference abstracts and online resources, with a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
947
7
28

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,160 publications
(1,014 citation statements)
references
References 27 publications
32
947
7
28
Order By: Relevance
“…More recently, Spikes and colleagues demonstrated macaques infected with SIV and injected with morphine have markedly increased pulmonary vascular changes, with increased numbers of apoptosisresistant cells and advanced plexiform lesions, when compared with morphinetreated, uninfected animals or SIV-infected animals (14). Although in our study IDU was not associated with PASP or PH, it is unknown whether in humans HCV adds another "hit" to the pulmonary vasculature by acting synergistically with injection drugs and/or HIV infection, especially because HIV-HCV coinfection is frequently transmitted via IDU (15,29).…”
Section: Original Researchcontrasting
confidence: 52%
See 1 more Smart Citation
“…More recently, Spikes and colleagues demonstrated macaques infected with SIV and injected with morphine have markedly increased pulmonary vascular changes, with increased numbers of apoptosisresistant cells and advanced plexiform lesions, when compared with morphinetreated, uninfected animals or SIV-infected animals (14). Although in our study IDU was not associated with PASP or PH, it is unknown whether in humans HCV adds another "hit" to the pulmonary vasculature by acting synergistically with injection drugs and/or HIV infection, especially because HIV-HCV coinfection is frequently transmitted via IDU (15,29).…”
Section: Original Researchcontrasting
confidence: 52%
“…Intravenous morphine exposure and simian immunodeficiency virus (SIV) act synergistically to promote pulmonary vasculopathy in macaques (14). Injection drug use (IDU) is the most common mode of HCV transmission in the United States, and HIV-HCV coinfection rates among patients with IDU are greater than 50% (15,16). More recently, it has been suggested that interferon (IFN), historically the mainstay of therapy for chronic HCV infection, may be a unique risk factor for drug-induced pulmonary arterial hypertension (2,(17)(18)(19).…”
mentioning
confidence: 99%
“…HCV infection is highly prevalent among people who inject drugs (PWID), varying from around 60-80% of PWID infected across national samples in Western Europe, the USA and Canada (Nelson et al, 2011). Early diagnosis of HCV provides the best opportunity for effective medical support and the prevention of further transmission (Corey, MendezNavarro, Gorospe, Zheng, & Chung, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…F Indication group 2: Persons at increased risk of non-occupational exposure.Examples: Persons living together with HBsAg carriers [11,12,13], persons at high risk of acquiring hepatitis B by sexual contact [11,14,15], people who inject drugs [14,16,17], prison inmates [18,19,20], psychiatric inpatients [21,22]. F Indication group 3: Persons at increased risk of occupational exposure.Examples: Health care personnel (HCP) at risk of exposure (including trainees, laboratory personnel, cleaning personnel) [23,24,25], first aiders [26,27], police officers [29], personnel of facilities where an increased prevalence of HBV-infected persons is likely to be present (e.g., correctional facilities, asylum seeker shelters, homes for the handicapped) [18,19,20,27,28,29].…”
Section: Schlüsselwörtermentioning
confidence: 99%